(untitled) (Medico Legal Update, 2020)
Human development is a process of change that occurs throughout life. In adulthood, there are many changes in as such as cognitive, socio-emotional and physical changes. Body image is an individual experience in the form of perceptions of body shape and weight, as well as behaviours that lead to an individual’s evaluation of his physical appearance. Body image in women is very influential on their psychological factors such as self-esteem, self-compassion and psychological well-being. Sample of this research consisted of as many as 100 female excersicer. The research was conducted in Lapangan Merdeka, Lapangan Cadika, and Lapangan Teladan, Medan. Data were analysed by using simple logistic regression test and multiple logistic regression. The results of bivariate analysis found, the variables of self-esteem and self-compassion have an influence on body image in female exercisers with the value p<0.05. From the results of multivariate analysis, it is obtained that the value p>0.05, which means there is no relationship between self-esteem, self-compassion, and psychological well-being to body image. The results show that there is no relationship between self esteem, self-compassion and psychological well-being to body image in female exerciser, these variables do not have a dominant influence meaning, all the three variables have the same influence on body image. Further findings show that self-esteem has a greater influence to body image on female exerciser.